The Relevance of Contemporary Epistemology on Existing Knowledge: A Critical Analysis of Western Scientific Worldview according to al-Attas Perspective - Arroisi, Jarman; Zarkasyi, Hamid Fahmy; Roini, Winda (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
The progress of modern science and technology is considered very significant and provides convenience in every aspect. However, science has become the biggest challenge because it requires relevance to religion. The disparity between science and religion creates a dilemma, resulting in the secularization of science. This study aims to critically analyze the epistemology of Western science from the perspective of Al-Attas, which is specifically considered problematic by him. The method used in this research was content analysis, while the approach used was a critical approach. The results of this study prove that the paradigm of science is closely related to worldview. This proves that modern science and technology are not neutral and devoid of values, including religion. This has an impact on changing the way humans view and think about science and life, resulting in the deconsecration of value, desacralization, and disenchantment of nature. To map out the epistemological and Western worldview problems, al-Attas offers the Islamization of contemporary science and the epistemology of Islamic science to answer the problem of the existence of contemporary science epistemology.